DIRECT SPEECH ACTS, FACE THREATENING TOWARDS THE ELDERLY AND POLITENESS IN THE SPEECHES OF INDONESIAN CAREWORKERS - Putu Dewi Merlyna Yuda Pramesti (International Journal of Linguistics and Discourse Analytics, 2020)
This paper aims at examining the relationship between direct speech acts and face threatening towards the elderly and the politeness of the language used by the Indonesian careworkers in the nursing home for the elderly in Japan. This study of speech is a research object in pragmatics which is frequently examined beside other pragmatics phenomena, like implicatures and maxim flouting. The subjects of this study are 68 Indonesian careworkers who work in the elderly nursing homes in three regions, namely Yokohama, Toyohasi and Okayama, Japan. Those participants consist of 63 female and 5 male careworkers. Direct speech act is the type of speech act mostly used by the careworkers in their interaction with the elderly. From 285 conversation data collected, 260 of them contain direct speech acts. The data collection is conducted by recording the communication process between the two participants on daily basis for three months. The recording is done in a few locations (settings) to result in a comprehensive discussion. From the analysis it could be concluded that direct speech acts are frequently used by the Indonesian careworkers to ease the communication process, reduce the social distance between the two interactants, and promptly tell about the intentions of the speeches. The direct speech acts used include interrogative, declarative and imperative types. The functions are directive and representative. The direct speech acts used by the careworkers do not threaten the faces of the elderly, proven by the harmonious communication of both interactants.